Musculoskeletal Disorders Prevalence in Nurses at a Private Hospital in West Java Indonesia - Jehosua, Willy Andriano; Kakerissa, Netty; Gea, Daniel Putra; Eka, Ni Gusti Ayu (Jurnal Kedokteran Meditek, 2024)
Musculoskeletal disorders are prevalent among healthcare professionals, notably registered nurses. Typically, hospital nurses work long hours in awkward positions, bending and twisting. This study aimed to identify hospital nurses' musculoskeletal disorder complaints. This study was a cross-sectional study and conducted at a private hospital in West Java. This study recuited nurse respondents consisted of 73% were female nurses, with an average age of 27.66 ±3.56 years. The nurse respondents reported mild to severe pain based on Nordic Musculoskeletal Disorder Survey. This study found that there were 41% of the nurses reported mild pain in the lower neck, 51% reported moderate pain in the waist, and 12% reported severe pain in the waist. Overall, nurses in the inpatient unit dominates the middle part of the body complaints. Musculoskeletal disorder complaints from nurses needed additional assessment and intervention to improve nurses’ quality of life.